Nutritional Iron Deficiency: The Role of Oral Iron Supplementation - Lachowicz, J.I.; Nurchi, V.M.; Fanni, D.; Gerosa, C.; Peana, M.; Zoroddu, M.A. (Current Medicinal Chemistry, 2014)
Nutritional iron deficiency represents a relevant health problem mainly in developing countries. Children and pregnant women represent the main target of this disease, and the low amount of bio-available iron mostly depends on plant-based diets. Iron deficiency may have serious consequences, with severe impairment of the immune function leading to infectious diseases. The brain development in embryos and fetuses during gestation can be greatly affected by iron deficiency of the mother with heavy outcomes on the cognition status of children. A better understanding of molecular pathways involved in iron absorption and metabolism are the basis for new strategies for developing a therapy for iron deficiency. Different therapeutic strategies are summarized, and iron fortification appears the best tool.
Keywords: iron-fortified food